2012
DOI: 10.1007/s10484-012-9185-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heart Rate Variability Biofeedback on Performance Psychology of Basketball Players

Abstract: Coping with pressure and anxiety is an ineluctable demand of sports performance. Heart rate variability (HRV) Biofeedback (BFB) shall be used as a tool for self regulating physiological responses resulting in improved psycho physiological interactions. For further analysis, the present study has been designed to examine the relationship between anxiety and performance and also effectiveness of biofeedback protocol to create stress-eliciting situation in basketball players. Thirty basketball players of universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 15 publications
(19 reference statements)
1
95
0
6
Order By: Relevance
“…Heart Rate Variability (HRV) refers to the beat-to-beat changes in the duration of RR intervals (time between beats) in the Electrocardiogram (ECG) [25]. HRV has been suggested to be a reliable assessment of autonomic function, an index of cardiovascular adaptability, and indicative of autonomic or sympathovagal balance [26][27][28]. According to Appelhans and Luecken, high HRV reflects improved adaptability of physiological arousal, in addition to a greater capacity for regulated emotional responding [29].…”
Section: The Use Of Heart Rate Variability Biofeedback and Related Phmentioning
confidence: 99%
See 4 more Smart Citations
“…Heart Rate Variability (HRV) refers to the beat-to-beat changes in the duration of RR intervals (time between beats) in the Electrocardiogram (ECG) [25]. HRV has been suggested to be a reliable assessment of autonomic function, an index of cardiovascular adaptability, and indicative of autonomic or sympathovagal balance [26][27][28]. According to Appelhans and Luecken, high HRV reflects improved adaptability of physiological arousal, in addition to a greater capacity for regulated emotional responding [29].…”
Section: The Use Of Heart Rate Variability Biofeedback and Related Phmentioning
confidence: 99%
“…Findings demonstrated that those in the HRV BFB group achieved significantly greater increases in low-frequency HRV and health-related quality of life indices (i.e., vitality, bodily pain, and social functioning) across sessions compared to their control counterparts. In the sport realm, HRV BFB has been implemented for performance enhancement and emotional self-regulation [28]. Researchers have demonstrated its efficacy to improve psychomotor performance, cognitive and psychological states, and physiological functioning [28].…”
Section: The Use Of Heart Rate Variability Biofeedback and Related Phmentioning
confidence: 99%
See 3 more Smart Citations